Hollow‐Out Patterning Ultrathin Acoustic Metasurfaces for Multifunctionalities Using Soft fiber/Rigid Bead Networks. (15th July 2018) - Tang, Hanchuan; Chen, Zhesi; Tang, Ni; Li, Shuaifeng; Shen, Yaxi; Peng, Yugui; Zhu, Xuefeng; Zang, Jianfeng
Abstract: Acoustic metasurfaces that can manipulate and control sound waves at 2D subwavelength scales open new avenues to unusual applications, such as asymmetric transmission, super‐resolution imaging, and particle manipulation. However, the long‐standing goals of pushing frontier metamaterials research into real practice are still severely constrained by cumbersome configuration, large acoustic loss, and rigid structure of the existing metamaterials. An ultrathin metasurface (10–300 µm in thickness, up to ≈λ/650, λ the wavelength) that is capable of imparting sound wave with a nontrivial phase shift with high transmittance (>80%) in the range of 5–30 kHz is fabricated here. The metasurface is comprised of a porous network of soft polymer fiber/rigid beads that are physically equivalent to crosslinked spring‐mass resonators. Moreover, the traditional paper‐cutting art to carve the ultrathin metasurface into hollow‐out patterns is incorporated, resulting in a variety of remarkable functions, including acoustic vortex, focusing, and super‐resolution. The hollow‐out patterning approach innovates the traditional one‐step metadevice fabrication process into two separated steps: 1) fabrication of ultrathin metasurfaces; 2) hollow‐out patterning of metasurfaces. The strategy opens an avenue to mass production of acoustic metadevices, shedding light on the applications of the metamaterials in acoustic cloaking, acoustic positioning, and particle manipulation. Abstract : An ultrathin metasurface (10–300 µm in thickness, up to ≈λ/650) that is capable of imparting sound waves with a nontrivial phase shift and high transmittance (>80%) in broadband is fabricated. Moreover, the ultrathin metasurface is carved into hollow‐out patterns by paper‐cutting art, resulting in a variety of remarkable functions, including acoustic vortex, focusing, and super‐resolution.